Quality Control Testing of Chloramphenicol Eye Drops - Kamour, Ruwida; Ahmed Abdulaziz; Abdulsalam Alajeel (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and aims. Choramphenicol is one of important therapeutic options for bacterial conjunctivitis. Its eye drop formulation must possess standards of good quality and sterility. The drug is very sensitive to light and temperature and must be stored between 2 and 8 ᵒ C. This study included testing two of the marketed eye-drops formulations of chloramphenicol of two different origins to ensure quality and efficacy of the drugs. Methods. The test methodology followed same pharmacopeial tests to evaluate both physical and chemical aspects of the drugs tested. Identification tests and assay were carried out. Results. Both products passed the identification tests however, there were different findings and the product from Pakistani company failed to comply with BP limits for the pH range and assay. Conclusion. It is of great importance to check on some drugs to see if affected during transport and distribution by testing samples collected randomly from pharmacies. الخلفية والأهداف. يعد الكلورامفينيكول أحد الخيارات العلاجية المهمة لالتهاب الملتحمة الجرثومي. يجب أن تتمتع تركيبة قطرات العين بمعايير الجودة الجيدة والتعقيم. الدواء حساس للغاية للضوء ودرجة الحرارة ويجب تخزينه بين 2 و 8 درجات مئوية. تضمنت هذه الدراسة اختبار تركيبتين من قطرات العين المسوقة من الكلورامفينيكول من أصلين مختلفين لضمان جودة وفعالية الأدوية. الطرق. اتبعت منهجية الاختبار نفس الاختبارات الدوائية لتقييم الجوانب الفيزيائية والكيميائية للأدوية التي تم اختبارها. تم إجراء اختبارات التعريف والتحليل. النتائج. اجتاز كلا المنتجين اختبارات التعريف، ومع ذلك، كانت هناك نتائج مختلفة وفشل المنتج من الشركة الباكستانية في الامتثال لحدود BP لنطاق الأس الهيدروجيني والتحليل. الاستنتاج. من المهم للغاية التحقق من بعض الأدوية لمعرفة ما إذا كانت تتأثر أثناء النقل والتوزيع عن طريق اختبار العينات التي تم جمعها عشوائيًا من الصيدليات